TINDAK TUTUR ILOKUSI DALAM PERCAKAPAN ANTARA DOSEN DAN MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA DAN SASTRA INDONESIA UMN AL WASHLIYAH - Sutarini, Sutarini; Sutikno, Sutikno; Kartolo, Rahmat (Linguistik : Jurnal Bahasa dan Sastra, 2023)
The use of Indonesian in teaching and learning interactions is a form of communication. Interactions carried out by students to lecturers can be in the form of conversations, dialogues, or questions about everything related to what students are feeling or complaining about. The speech acts used in discussions vary widely because they generally come from different regions. It is this impression that makes researchers interested in studying illocutionary speech acts in the lecture process. This study specifically aims to describe the use of illocutionary speech acts between students and lecturers of the Indonesian language and literature education study program at UMN Al Washliyah. The method used in this research is descriptive qualitative. The subjects of this study were students and lecturers in learning interactions in Indonesian language and literature education study program classes. The object of research is speech acts, especially illocutionary speech acts which are forms of student speech to lecturers. In this study, data collection was carried out using two methods, namely (1) the listening method and (2) the speaking method. The results of the study show that illocutionary speech acts between lecturers and students during the teaching and learning process take place in the form of declaration, representative, expressive, directive and commissive speech acts.